KARAKTERISTIK SUHU PERMUKAAN LAUT DAN HUJAN DI INDONESIA - Yusuf Awaludin, Muhammad (Jurnal Harpodon Borneo, 2011)
Sea surface temperature (SST) and rainfall characteristics in Indonesia are reviewed and are discussed.  The paper focuses on the following topics : SST and rainfall characteristics ; and coupled SST-rainfall. It concludes that SST has its sensitivity to rainfall with the peak during April and the lowest during August.  Meanwhile, rainfall has three different regions with decreasing trend in the last few decades.  SST-rainfall interaction possible related to large scale climate drivers.  Keywords  :  SST, rainfall, climate.